ANTISIPASI GANGGUAN PMT PENYULANG SAMBONG AKIBAT BINATANG DENGAN PENGHALANG PANJAT SENG DI PT. PLN ULP JOMBANG - Trisno Sanyoto; Muhammad Septian Wijaya; Agus Subandono; Ida Ernawati; Setyo Hartono (LPPM Politeknik Pratama Kendal, 2022)
The increasing demand for electrical energy should be supported by efforts to improve the quality of service to customers. The service is said to be unsatisfactory if the electricity supply that is distributed often experiences blackouts which causes customers to be unable to use electricity for a certain period of time. In addition to customers who were harmed due to the non-channeling of electricity, the company's performance value, especially PT. PLN (Persero) ULP Jombang, decreased compared to other ULP. PT. PLN (Persero) ULP Jombang is currently trying to provide the best service by overcoming 20 kV medium voltage power grid disturbances and increasing the company's performance value. PMT disturbance is one of the company's performance values. From a total of 13 feeders in the work area of PT. PLN (Persero) ULP Jombang, PMT disturbances caused by animals occur in the sambong feeder with 2 times the PMT disturbance in 2021. One way to anticipate is not to Repeated PMT disturbances in the sambong feeder, namely by installing zinc climbing barriers at points prone to animals.